Actions of Harmonia axyridis (Coleoptera: Coccinellidae) alkaloids on vertebrate and invertebrate nicotinic acetylcholine receptors - Patel, Rohit (2012)
The productivity of livestock and crops worldwide is dramatically reduced by pest organisms and pesticides are an important front-line control. Current pesticides raise environmental concerns and are threatened by the development of resistance so there is a great need for alternatives.